Performance Evaluation and QoS Optimization of LTE-WLAN Aggregation in Small Cell Networks - Wijanto, Eddy; Sutanto, Kevin (ELKHA : Jurnal Teknik Elektro, 2025)
The rapid surge in mobile data traffic continues to strain cellular networks, especially in dense urban areas where spectrum resources are limited. Long Term Evolution"“Wireless Local Area Network (LTE-WLAN) Aggregation (LWA), standardized in 3GPP Release 13, provides a promising approach by enabling simultaneous use of licensed LTE and unlicensed Wi-Fi bands. This study evaluates the performance and quality of service (QoS) of LWA in a small cell setting, focusing on the optimization of LTE-to-WLAN traffic ratios. A practical testbed was deployed using an ITRI LTE small cell, a Wi-Fi access point, and dual-connectivity user equipment (UE). Experiments were conducted under multiple aggregation ratios (1:1, 1:3, 2:1), user mobility scenarios, and real-world applications such as YouTube streaming. Key QoS indicators, including throughput, jitter, and bandwidth, were measured with iPerf and Network-Draw tools. Results indicate that a 1:3 LTE-to-WLAN ratio consistently delivers the best throughput and efficient spectrum use, particularly when UEs are located near the Wi-Fi access point. Moreover, application-level buffering and adaptive bitrate mechanisms successfully mitigate lower-layer fluctuations, ensuring seamless video playback. The novelty of this work lies in its real-world dual-user experiments, demonstrating how spatial proximity and traffic distribution jointly influence QoS in small cell environments, thereby offering practical insights for next-generation heterogeneous networks. These findings provide actionable guidance for network operators, showing how optimal traffic ratios and user proximity considerations can be applied to improve QoS, reduce congestion, and support high-bandwidth applications in real-world small cell deployments.